2020
DOI: 10.3389/fmed.2020.00527
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Pulsed Lavage and Antimicrobial Therapy Against Staphylococcus aureus Biofilms in an in-vitro Model

Abstract: Background: Prosthetic joint infections (PJI) are difficult to treat complications of joint arthroplasty. Debridement with implant retention is a common treatment strategy and frequently involves the use of pulsed lavage (PL). However, PL effects on biofilms and antibiotic activity have been scarcely studied in-vitro. We report the effects of PL, vancomycin or flucloxacillin used independently or in combination against Staphylococcus aureus biofilms. Methods: Biofilms of 3 methicillin-susceptible (MSSA) and of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…CLSM also showed that the biofilm had been reduced to a monolayer of cells on the surface, and the remaining cells appeared to be mostly viable after PL. These findings are consistent with previous studies that reported approximately two-log reduction in cell numbers following PL [ 20 , 26 ]. Knecht et al [ 20 ] have demonstrated that PL reduced the CFU count of strain of biofilms by approximately two orders of magnitude, from an initial cell count on the metal surface of approximately 10 9 CFU/cm 2 .…”
Section: Discussionsupporting
confidence: 94%
“…CLSM also showed that the biofilm had been reduced to a monolayer of cells on the surface, and the remaining cells appeared to be mostly viable after PL. These findings are consistent with previous studies that reported approximately two-log reduction in cell numbers following PL [ 20 , 26 ]. Knecht et al [ 20 ] have demonstrated that PL reduced the CFU count of strain of biofilms by approximately two orders of magnitude, from an initial cell count on the metal surface of approximately 10 9 CFU/cm 2 .…”
Section: Discussionsupporting
confidence: 94%
“…The plates were incubated for 24 h (ATCC 33591 and ATCC 35984) or 48 h (ATCC 47076) at 37°C, with a constant orbital shaking of 50 rpm. In the case of strain ATCC 47076 biofilms, the medium was changed after 24 h. These culture times were selected as they allowed the biofilms to reach steady states over the study period and were determined in previous growth kinetic experiments for S. aureus (14). The culture duration period for S. epidermidis was derived from these results.…”
Section: Biofilm Culturementioning
confidence: 99%
“…Another novel strategy is the use of engineered cationic amphipathic peptide, WLBU2, as an irrigation adjunct to be used during the surgical debridement of BRII; WLBU2 has been previously shown to eliminate biofilms and create culture negative implants in 30 min, and in a recent in vitro and in vivo murine infection model, WLBU2 solution was able to markedly reduce S. aureus biofilm on implant material [128]. The use of pulsed-lavage irrigation fluid in combination with physiological concentrations of antibiotic agents, vancomycin and flucloxacillin, was demonstrated in vitro to reduce the bacterial load of biofilms adhered to implant materials but did not demonstrate complete eradication [14].…”
Section: Biofilm Eradication Strategiesmentioning
confidence: 99%
“…Bacterial biofilms display emergent properties: that is, properties that are not predictable from study of the planktonic cells from which they emerge [12]. These properties give the biofilms a significant survival advantage, making them extremely resilient to host immune or conventional anti-microbial therapies; they have been shown to be up to 1000× more resistant to antibiotic eradication, which ultimately results in the recalcitrance and recurrence of biofilm-related implant infection [13][14][15][16].…”
Section: Bacterial Biofilm In Implant-related Infectionsmentioning
confidence: 99%
See 1 more Smart Citation